2015
DOI: 10.1007/s10661-015-4718-9
|View full text |Cite
|
Sign up to set email alerts
|

Historic change in catchment land use and metal loading to Sydney estuary, Australia (1788–2010)

Abstract: Sydney estuary has a long history of environmental degradation and is one of the most modified water ways in Australia due to a highly urbanised catchment (~77 %) and a high population (4.6 million). The objectives of the present study were to map historical land use change from European settlement (1788) to 2010 to determine catchment evolutionary pathways and to estimate catchment loading (total suspended solids, Cu, Pb and Zn) to the estuary over this period. Land use distribution in Sydney catchment, deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(5 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Stormwater runoff can contain metal contaminants from a variety of sources: metal [Cu and galvanized] roofs (Charters et al 2016 ; Gasperi et al 2012 ), scrap metal yards (Aryal et al 2010 ), combined sewer system pipe erosion (Gasperi et al 2012 ), suburban stormwater catchments (e.g., gutters) (Gasperi et al 2012 ), and/or vehicle parts (e.g., brakes, tires and engines) (Aryal et al 2010 ). Many researchers have shown that the primary source of heavy metals (specifically Cu and Zn) released during rain events is from urban roadways, due to deposition and accumulation from vehicle traffic including brake pad wear, engine parts, and tire wear (Aryal et al 2010 ; Birch et al 2015 ; Charters et al 2016 ; Huber et al 2016 ). Additionally, McKee and Gilbreath ( 2015 ) showed a correlation between turbidity and trace elements, which is reiterative of the findings surrounding road-deposited sediment as a source of heavy metals within stormwater runoff (Aryal et al 2010 ; Charters et al 2016 ; Gasperi et al 2012 ; Zgheib et al 2012 ; Zhang et al 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Stormwater runoff can contain metal contaminants from a variety of sources: metal [Cu and galvanized] roofs (Charters et al 2016 ; Gasperi et al 2012 ), scrap metal yards (Aryal et al 2010 ), combined sewer system pipe erosion (Gasperi et al 2012 ), suburban stormwater catchments (e.g., gutters) (Gasperi et al 2012 ), and/or vehicle parts (e.g., brakes, tires and engines) (Aryal et al 2010 ). Many researchers have shown that the primary source of heavy metals (specifically Cu and Zn) released during rain events is from urban roadways, due to deposition and accumulation from vehicle traffic including brake pad wear, engine parts, and tire wear (Aryal et al 2010 ; Birch et al 2015 ; Charters et al 2016 ; Huber et al 2016 ). Additionally, McKee and Gilbreath ( 2015 ) showed a correlation between turbidity and trace elements, which is reiterative of the findings surrounding road-deposited sediment as a source of heavy metals within stormwater runoff (Aryal et al 2010 ; Charters et al 2016 ; Gasperi et al 2012 ; Zgheib et al 2012 ; Zhang et al 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, hydrodynamic factors such as wind, tides, freshwater input, morphology, and geometry may influence water quality (Zarzuelo et al, 2023). An increase in population and industrialization in urban areas have impacted land-use change and water pollution (Tanaka et al, 2021), specifically in South East Asian, such as Malaysia (Zaki et al, 2021) and Vietnam (Pham et al, 2021), and India (Singh et al, 2021), Japan (Chao et al, 2020), China (Cai et al, 2021), and Australia (Birch et al, 2015). Those mangrove functions and problems occurred in Tuntang, as reported by Irsadi et al (2019Irsadi et al ( , 2020.…”
Section: Introductionmentioning
confidence: 99%
“…Urbanised environments broadly comprise human-constructed spaces such as buildings and roads, and vegetated patches, sometimes referred to as 'green spaces' (Adams et al 2006). Extensive land use change in Sydney, Australia's oldest and most populous city, has been brought on by rapid population increase and a long history of industrial activity since European settlement (Birch et al 2015;Reid 2020). The Sydney metropolitan area has an estimated human population of over 5 million, residing within an area of approximately 12 367 km 2 .…”
Section: Introductionmentioning
confidence: 99%